The complete stories of the wizard of Oz volume 2 - Baum, L. Frank (Popular UK Pte Ltd, 2019)
In the words of the author himself, he wanted to create a 'modernized fairy tale' and more than a hundred year later, how prophetic his words are. The Complete Stories of the Wizard of Oz Volume 2 is a magisterial work in which seven stories from the Oz series are featured. The joy, wonderment and magic which the stories of Oz bring in this volume will delight teenagers and adults alike. Like a timeless tale that has traversed generations the stories of OZ are an enduring past of our shared literary history. Magical in narration and seminal in scope, The Complete stories of the Wizard of Oz will leave readers of all ages delighted by its sheer illustrative depth and fantastic storytelling.